Genome assembly of the Harbor seal Phoca vitulina ... - Nebenführ, Marcel; Arnason, Ulfur; Janke, Axel (GigaScience Database, 2024)
The harbour seal ( Phoca vitulina ) is classified as a small phocid seal. It is notable for having the most extensive geographical distribution of any seal species, occupying coastal waters that extend from temperate to polar regions in the Northern Hemisphere, often hauling out in groups that can consist of several hundred individuals. The population of harbour seals in the North Atlantic is estimated to be around 200,000. We present a publicly available genome assembly of the Harbor seal Phoca vitulina , with 47 Gb (~20.5-fold coverage) of sequence data. The complete assembly spans 2.3 Gb, with contig N50 of 12 kb and scaffold N50 of 173 Mb. The BUSCO analysis indicates a completeness of 89.3%. ...